Reconstruction of vocational high school physics instructional materials - Ira Herli Khoeriah; Ade Gafar Abdullah; Budi Mulyanti (Universitas PGRI Kanjuruhan Malang, 2020)
Instructional materials for static electricity and dynamic electricity for Physics subjects in Vocational High Schools are not in accordance with the scope of the material contained in the Electronics Department: (1) The purpose of this study is to provide an overview of the teaching materials of static electricity and dynamic electricity in Physics in the Electronics Department; (2) Qualitative Content Analysis Method was used to explore the contents of seven book titles with different publishers and is strengthened through inter-views with Physics teachers in the Department of Electronics. In the process of analyzing the content of the contents of this textbook used Atlas.ti computer software; (3) The findings show that the content in the Vocational High School Physics books pub-lished by several publishers does not yet have specific conformity with the Department of Electronics; (4) conclusion. There are code relating to the content content, researchers only specify it into 39 code titles in the VHS Physics Textbook. from qualitative analysis. The level of compatibility of the content of the material with the 2013 Revised Curriculum was 42.86%, the availability of pictures was 75%, examples of questions from the equa-tions of each series were 85.71%, the suitability of the practicum with the Electrical Clump was 14.29%. content conformity with the Revised 2013 Curriculum and electro majors has a slightly low percentage of 42.86%. So in this study, the authors reconstruct VHS Physics teaching materials for the Electrical Department and also make VHS Physics teaching materials for the Electrical Clump.